Training elite youth soccer players: area per player in small-sided games to replicate the match demands - Riboli, A.; Olthof, S. B. H.; Esposito, F.; Coratella, G. (Biology of Sport, 2022)
The aim was to determine the area per player (ApP, m2 × player) in small- or large-sided games to replicate the official match demands in elite youth soccer players. Two hundred and twenty-eight players (U15 = 36, U16 = 48, U17 = 49, U18 = 37 and U19 = 58) were monitored during both training (12 183 individual samples) and matches (683 individual samples) across five seasons. Relative (m × min-1) total (TD), high-speed running (HSR), very high-speed running (VHSR), sprint and acceleration/deceleration (Acc/Dec) distance were collected. Between-category and between-position comparisons were performed. Area per player was moderately correlated (P < 0.05) with TD (r = 0.401), large (r = 0.621) with HSR, and very largely with VHSR (r = 0.744) and sprint (r = 0.723). An inverse small (r = -0.232; P = 0.039) correlation for Acc/Dec was found. The area per player to replicate the match demands was 158 ± 18, 182 ± 32, 197 ± 37, 212 ± 42 and 156 ± 25 m2 × player for TD, HSR, VHSR, sprint and Acc/Dec, respectively. Moderate to very large (ES: 0.79 to 4.66) differences in the area per player across metrics were observed, with sprint > VHSR > HSR > TD = Acc/Dec. Trivial to very large (ES: 0.01 to 2.67) between-category differences in area per player across the same metric were found, with U15 and U16 requiring a larger area per player than other age categories. These findings may help practitioners to recreate the desired external load outcomes with regards to positional match-play demands using specific area per player in small- or large-sided games in youth elite soccer players from U15 to U19.